Neoliberalna reforma emerytalna – po kilkunastu latach - Kalina-Prasznic, Urszula (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
The article concerns the results of the neoliberal pension reform. The author substantiates the statement, that current markets can speculate on the level of large scale. On the ground of the elucidation of scientific legal literature the author makes her own propositions as to the improvement of current legislation of Ukraine.
Keywords: reforma emerytalna; neoliberalizm; ustawodawstwo Ukrainy